Bounds for Estimators of Ergodic Averages - Mesón, Alejandro Mario (2013)
We consider different ergodic averages and estimate the measure of the set of points in which the averages apart from a given value. The cases considered are empirical measures of cylinders in symbolic spaces and averages of maps given a kind Lyapunov exponents, in a such spaces. Besides we obtain bounds for the fluctuations of ergodic averages from amenable action groups. The bounds obtained are valid for any ¨time¨, not only, like in case of large deviations, for asymptotic values.